Genome Analysis of Clostridium difficile PCR Ribotype 014 Lineage in Australian Pigs and Humans Reveals a Diverse Genetic Repertoire and Signatures of Long-Range Interspecies Transmission - Knight, Daniel R.; Squire, Michele M.; Collins, Deirdre A.; Riley, Thomas V. (Frontiers in Microbiology, 2017)
Clostridium difficile PCR ribotype (RT) 014 is well established in both human and porcine populations in Australia, raising the possibility that C. difficile infection (CDI) may have a zoonotic or foodborne aetiology. Here, whole genome sequencing and high-resolution core genome phylogenetics were performed on a contemporaneous collection of 40 Australian RT014 isolates of human and porcine origin. Phylogenies based on MLST (7 loci, STs 2, 13 and 49) and core orthologous genes (1,260 loci) showed clustering of human and porcine strains indicative of very recent shared ancestry. Core genome single nucleotide variant (SNV) analysis found 42% of human strains showed a clonal relationship (separated by ≤ 2 SNVs in their core genome) with one or more porcine strains, consistent with recent inter-host transmission. Clones were spread over a vast geographic area with 50% of the human cases occurring without recent healthcare exposure. These findings suggest a persistent community reservoir with long-range dissemination, potentially due to agricultural recycling of piggery effluent. We also provide the first pan-genome analysis for this lineage, characterising its resistome, prophage content and in silico virulence potential. The RT014 is defined by a large ‘open’ pan-genome (7,587 genes) comprising a core genome of 2,296 genes (30.3% of the total gene repertoire) and an accessory genome of 5,291 genes. Antimicrobial resistance genotypes and phenotypes varied across host populations and ST lineages and were characterised by resistance to tetracycline (tetM, tetA(P), tetB(P) and tetW), clindamycin/erythromycin (ermB) and aminoglycosides (aph3-III-Sat4A-ant6-Ia). Resistance was mediated by clinically important mobile genetic elements, most notably Tn6194 (harbouring ermB) and a novel variant of Tn5397 (harbouring tetM). Numerous clinically important prophages (Siphoviridae and Myoviridae) were identified as well as an uncommon accessory gene regulator locus (agr3). Conservation in the pathogenicity locus and S-layer correlated with ST affiliation, further extending the concept of clonal C. difficile lineages. This study provides novel insights on the genetic variability and strain relatedness of C. difficile RT014, a lineage of emerging One Health importance. Ongoing molecular and genomic surveillance of strains in humans, animals, food and the environment is imperative to identify opportunities to reduce the overall CDI burden.